Interpretation and application of Article 404 of the Criminal Procedure Code of Ukraine on court initiative: case law of the Criminal Court of Cassation - I. V. Hloviuk (Law and Safety)
The issue of interpretation of Part 3 of Art. 404 of the Criminal Procedure Code of Ukraine regarding the initiative of the court of appeal in the examination of evidence has been investigated: at the request of the parties to the court proceedings, the court of appeal is obliged to re-examine the circumstances established during criminal proceedings, provided that they were not fully or with violations investigated by the court of first instance, and may examine evidence which was not investigated by the court of first instance, only if the parties to the court proceedings request such examination. This is due to the opposite interpretation of this provision by the courts, including the Criminal Court of Cassation of the Supreme Court. The accuracy of the literal interpretation of this provision has been argued.